Isolation of five different primary cell types from a single sample of human skin - Sylwia Kabacik (STAR Protocols, 2022)
Summary: We have developed a technique to isolate primary keratinocytes, melanocytes, fibroblasts, preadipocytes, and microvascular endothelial cells from an individual sample of human skin. The protocol describes step-by-step instructions for processing, cells isolation, and culture of neonatal foreskin, with adaptation for more demanding adult tissues. The availability of multiple isogenic cell types derived from individual skin samples offers the ability to investigate various areas of biology, in the context of cell-type specificity without potential confounding influence of inter-individual or genetic differences.For complete details on the use and execution of this protocol, please refer to Holliman et al. (2017), Horvath et al. (2019), Horvath et al. (2018), Kabacik et al. (2018), Lowe et al. (2020), Lu et al. (2019), and Lu et al. (2018).